E-business, organizational innovation and firm performance in manufacturing SMEs: an empirical study in Spain - Soto-Acosta, Pedro; Popa, Simona; Palacios-Marqués, Daniel (Technological and Economic Development of Economy, 2016)
This paper extends previous studies on the organizational impact of Internet technologies by analyzing factors affecting e-business use and its effect on organizational innovation in manufacturing Small and Medium-Size Enterprises (SMEs). In addition, the mediating effect of organizational innovation on the relationship between e-business and firm performance is analyzed. Grounded in the Technology-Organization-Environment (TOE) theory and the Knowledge-Based View (KBV), this paper develops an integrative research model which analyzes those relations using partial least squares (PLS) structural equation modeling on a dataset of 175 Spanish manufacturing SMEs. Results suggest that e-business use emerges from technological and internal organizational resources rather than from external pressure. In addition, results show that e-business use contributes positively to firm performance through organizational innovation.First published online: 21 Sep 2015